A STUDY OF FINANCIAL FEASIBILITY OF MOANAMANI MICROHYDRO POWER PLANT (PLTMH) (A CASE STUDY IN EKEMANIDA VILLAGE, MOANAMI DISTRICT, DOGIYAI REGENCY) - Ira Widyastuti; Paseru R. L; Hery Dualembang; Eka P. Kombong; Herlina Sanggamele (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2026)
Micro Hydro Power Plants (PLTMH) with a capacity of <1MW are an alternative energy source to replace fossil fuels in remote areas, one of which is the PLTMH in Moanamani Distric, Papua Province, Indonesia, managed by PT. PLN (Ltd). Due to a construction collapse at the dam, the Moanamani Micro Hydro Power Plant is now sustaining damage that is harming other supporting facilities. Given the tight budget in the area, particularly in Dogiyai Regency, the goal of this study is to secure a capital finance and loan plan that can then be discussed by the pertinent stakeholders. This study analyzed the potentials of renewable energy and economic finance of the PLTMH, measuring the Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), Pay Back Period (PBP), and Break Event Point (BEP). The results showed that the debit of Tuka River could generate at least 65.50 kW of power and an annual energy of 50,546 kWh. The investment value of PLTMH at Moanamani Village was IDR 6,600,000,000, and the Cost of Goods Sold was IDR 336,384/kWh. Based on the economic calculation, the NPV of PLN Ltd was IDR 6,300,000,000, the NPV of the community was IDR 1,987,056,834, the IRR was -1,79%, the BCR was 0.32, the PBP was ± 20 years, and the BEP was ± 50 years. The development project of PLTMH with a funding scheme of 30% equity and 70% loan showed that the project was not financially feasible.